2017
DOI: 10.21065/1920-4159.1000247
|View full text |Cite
|
Sign up to set email alerts
|

Study of Antibiotics Prescribing Pattern in Paediatric Patients of Thamar Province, in Republic of Yemen

Abstract: The aim of this study was to determine the prescriptions pattern of antibiotic in paediatric in-patient department of General Thamar Hospital in Yemen. The method was prospective and observational study which was carried out for 2 months duration between March-April 2015. Patient's data was being recorded in a specific format and results were analysed by descriptive statistic and expressed as mean ± SD. The result was out of 148 patients, 95 prescriptions were taken antibiotics, where 59 were male child and 36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…The results indicated that the higher rate (19.2 %) were in the age group between 21-30 years, followed by the group with age between 31-40 years (11.5%). AbdulRazag [25] reported that the higher prevalence of brucella antibody in the group between 51-60 years (33.3%), followed by the female with age between 21-30 (20.6%) according to RBT. There were no significant differences between the RBT among female blood according to age (p>0.05).Anyhow, our results were compatible with [36] in India who found that the prevalence of brucellosis was higher in >35-50 years age group (middle-aged) (16.13%), compared to >20-35 years (young adults) (9.59%) and >50-65 years (elderly adults) (0.00%).…”
Section: Prevalence Of Human Brucellosis In Erbil Governorate Accordimentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that the higher rate (19.2 %) were in the age group between 21-30 years, followed by the group with age between 31-40 years (11.5%). AbdulRazag [25] reported that the higher prevalence of brucella antibody in the group between 51-60 years (33.3%), followed by the female with age between 21-30 (20.6%) according to RBT. There were no significant differences between the RBT among female blood according to age (p>0.05).Anyhow, our results were compatible with [36] in India who found that the prevalence of brucellosis was higher in >35-50 years age group (middle-aged) (16.13%), compared to >20-35 years (young adults) (9.59%) and >50-65 years (elderly adults) (0.00%).…”
Section: Prevalence Of Human Brucellosis In Erbil Governorate Accordimentioning
confidence: 99%
“…Statistical analysis using ChiSquare showed no significant difference at the level of 0.05 for the brucellosis existing in the human where the value of Chi-Square was (0.42) with the level of significance 0.52 (p> 0.05).According to age groups, the prevalence rate of brucella antibodies among male was high in age group between 31-40 years (10.3 %), followed by the group with age between 21-30 years (10.0% ), then from 41 to 50 years were (7.1%),after that from 51 to 60 years were (6.9%), finally the age group from 11 to 20 years were (3.3 %) (Table2).The obtained results indicated that there were no significant differences between the RBT among male blood according to age (p>0.05). In Yemen [25] noticed that the prevalence rate of Brucella infection among male was high (17.4%) in the age group between 31-40 years according to RBT. Also, table 3, show that the prevalence of Brucella infection in female blood according to age groups.…”
Section: Prevalence Of Human Brucellosis In Erbil Governorate Accordimentioning
confidence: 99%
“…7 Estimates from the review on antimicrobial resistance (2016) suggest that 89% of deaths related to AMR in 2050 will occur in Africa and Asia. 8 Studies have reported that 50%-85% of children receive antibiotics unnecessarily prescribed for viral infections such as the common cold, which are the major contributor to the misuse or overuse of antibiotics. 9 Pakistan is facing a pandemic of Antibiotic resistance due to the absence of scintillating monitoring of antibiotic prescribing and usage.…”
Section: Introductionmentioning
confidence: 99%